1990
DOI: 10.1144/gsl.sp.1990.050.01.03
|View full text |Cite
|
Sign up to set email alerts
|

Geological integration and evaluation of Northern Monagas, Eastern Venezuelan Basin

Abstract: Over the last 60 years, the Eastern Venezuelan Basin has been heavily explored with giant oil accumulations being developed in such areas as Oficina, Anaco, Quiriquire and the Orinoco Oil Belt in the states of Anzoategui and Monagas. Since 1986, interdisciplinary studies and seismic interpretations have led to discovery of a trend of deep structures on the northern flank of the basin, some of them beneath old early Tertiary producing fields. The first exploratory well, FUL-1, tested 12000 BOPD of 28 ~ API crud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…In this context, even the impressive discoveries of light oil in the Maturin sub-basin in the north, with more than ?5.0 B (billion: lo9) brl, constitute but a minor variation to the total basin reserves figure. Light oil, however, has an immediate, high economic value, and every effort is being undertaken to develop these reserves (Aymard et al, 1990;Prieto and Valdes, 1992). Active development is under-way, even where drilling depths of over 18,000 ft are required, and where over-pressures, tectonic-trap complications, reservoir variations, etc.…”
Section: The Eastern Venezuela Basinsupporting
confidence: 84%
“…In this context, even the impressive discoveries of light oil in the Maturin sub-basin in the north, with more than ?5.0 B (billion: lo9) brl, constitute but a minor variation to the total basin reserves figure. Light oil, however, has an immediate, high economic value, and every effort is being undertaken to develop these reserves (Aymard et al, 1990;Prieto and Valdes, 1992). Active development is under-way, even where drilling depths of over 18,000 ft are required, and where over-pressures, tectonic-trap complications, reservoir variations, etc.…”
Section: The Eastern Venezuela Basinsupporting
confidence: 84%
“…Caparo Fault) in the Mérida Andes during the PaleoceneEocene. Aymard et al (1990) showed that local fault controlled basins and local uplifts with truncation to the Jurassic level are overlain by Cenozoic molasse in the Apure Basin, but the age of the molasse is debated and thus it is not clear if this deformation is Palaeogene or Neogene. Nonetheless, the idea of a limited amount of Palaeogene dextral shear, during Lara Nappe emplacement, accords with the Maastrichtian onset of Caribbean subduction beneath Colombia.…”
Section: Maastrichtian -Palaeogene Expansion Of the Caribbean Plate Imentioning
confidence: 99%
“…During most of the Cretaceous the northern part of the South American plate was a passive margin bordering the proto-Caribbean sea-way, which was supplied with sediment derived from the south (Aymard et al, 1990). The Cretaceous-Paleogene passive margin sedimentary succession dips gently to the northwest and onlaps the Jurassic break-up unconformity (Di Croce et al, 1999).…”
Section: Sequence 1: Cretaceous-paleogenementioning
confidence: 99%